Shared Vision Among Acute Care Magnet® Hospital Nurses: Ordinal Confirmatory Factor Analysis. (February 2017) - Liu, Wen; Johantgen, Meg; Newhouse, Robin
Psychometric testing of the Shared Vision (SV) scale that measures team efforts toward common patient-centered goals was initially estimated among rural hospital nurse executives. The purpose of this study was to estimate the scale's reliability (internal consistency), convergent validity (Pearson correlation with Practice Environment Scale), and structural validity (ordinal confirmatory factor analysis) among acute care Magnet ® hospital nurses. The study sample included 289 nurses from 27 acute care Magnet® hospitals. The scale demonstrated acceptable estimates for internal consistency (Cronbach's α = .902, 95% confidence interval [CI] = [0.883, 0.919]), convergent validity ( r = .720, p < .001), and structural validity with a one-factor structure. The findings of this study supported the reliability and validity of the SV scale as a unidimensional construct in measuring SV among nurses in acute care Magnet® hospitals. Further testing among different nursing providers and health care settings is needed to accumulate evidence and expand use of the instrument.